mproving the ductility of externally supported reinforced beams With reinforced polymer fibers and their increase - السيد, احمد; عبد الرحمن عيسى (Latakia University Journal -Engineering Sciences Series, 2024)
In the last two decades, the use of advanced composite materials such as Fiber Reinforced Polymers (FRP) in strengthening reinforced concrete (RC) structural elements has been increasing. Research and design guidelines concluded that externally bonded FRP could increase the capacity of RC elements efficiently. However, the linear stress-strain characteristics of FRP up to failure and lack of yield plateau have a negative impact on the overall ductility of the strengthened RC elements. Use of hybrid FRP laminates, which consist of a combination of either carbon and glass fibers, or glass and aramid fibers, changes the behavior of the material to a non-linear behavior. This paper aims to study the performance of reinforced concrete beams strengthened by hybrid FRP laminates. This paper presents an experimental program conducted to study the behavior of RC beams strengthened with hybrid fiber reinforced polymer (HFRP) laminates. The program consists of twelve T-beams with overall dimensions equal to 460 x 300 x 3250-mm. The beams were tested under cyclic loading up to failure to examine its flexural behavior. Different reinforcement ratios, fiber directions, locations and combinations of carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP) laminates were attached to the beams to determine the best strengthening scheme. Different percentages of steel reinforcement were also used. An analytical model based on the stress-strain characteristics of concrete, steel and FRP was adopted. Recommendations and design guidelines of RC beams strengthened by FRP and HFRP laminates are introduced.